Analisis Karakteristik Parkir dan Kebutuhan Ruang Parkir di Kawasan Kuliner Pasar Lama Tangerang - Pusparani Windiar Raihana,; Nunung Widyaningsih, (Jurnal Indonesia Sosial Sains, 2021)
The problems contained in the Tangerang Old Market Culinary Area is a problem of irregular parking control congestion. One of the physical facilities in the area is the parking area of the road body. This study aims to analyze the characteristics of parking, road sections and provide alternative problem solving in accordance with the provisions of MKJI 1997. The result of this study is the volume of vehicles entering the parking area on Friday, November 13, 2020 as many as 34 cars and 41 motorcycles, Saturday, November 21, 2020 as many as 48 cars and 65 motorcycles and Sunday, November 27, 2020 as many as 41 cars and 61 motorcycles. The largest parking accumulation on Saturday as many as 11 cars occurred between 08:00-08:59 WIB and Sunday as many as 104 motorcycles occurred between 14:00-14:59 WIB. The average Saturday car park duration is 1.81 hours/vehicle and 2 hours/kend for motorcycles. On Saturday the largest car park index was 120.93% at 16:00-16:59 WIB and 108.26% for motorcycles occurred on Tuesday from 17:00 to 17:59 WIB. The largest PTO is 1 vehicle/SRP/observation time. Judging from the analysis of road sections for survey speed on Kisamaun road in the peak hours of morning, afternoon and afternoon have a level of service or Level of Service (LOS) namely D. This indicates that there is a level of vehicle flow in the afternoon Saturday, November 21, 2020 from 16:00 to 17:00 WIB.